Synthesis, Anticancer Activity, and In Silico Studies of 5-(3-Bromophenyl)-N-aryl-4H-1,2,4-triazol-3-amine Analogs - Mohamed Jawed Ahsan; Krishna Gautam; Amena Ali; Abuzer Ali; Abdulmalik Saleh Alfawaz Altamimi; Salahuddin; Manal A. Alossaimi; S. V. V. N. S. M. Lakshmi; Md. Faiyaz Ahsan (Molecules, 2023)
In the current study, we described the synthesis of ten new 5-(3-Bromophenyl)-N-aryl-4H-1,2,4-triazol-3-amine analogs (4a–j), as well as their characterization, anticancer activity, molecular docking studies, ADME, and toxicity prediction. The title compounds (4a–j) were prepared in three steps, starting from substituted anilines in a satisfactory yield, followed by their characterization via spectroscopic techniques. The National Cancer Institute (NCI US) protocol was followed to test the compounds’ (4a–j) anticancer activity against nine panels of 58 cancer cell lines at a concentration of 10−5 M, and growth percent (GP) as well as percent growth inhibition (PGI) were calculated. Some of the compounds demonstrated significant anticancer activity against a few cancer cell lines. The CNS cancer cell line SNB-75, which showed a PGI of 41.25 percent, was discovered to be the most sensitive cancer cell line to the tested compound 4e. The mean GP of compound 4i was found to be the most promising among the series of compounds. The five cancer cell lines that were found to be the most susceptible to compound 4i were SNB-75, UO-31, CCRF-CEM, EKVX, and OVCAR-5; these five cell lines showed PGIs of 38.94, 30.14, 26.92, 26.61, and 23.12 percent, respectively, at 10−5 M. The inhibition of tubulin is one of the primary molecular targets of many anticancer agents; hence, the compounds (4a–j) were further subjected to molecular docking studies looking at the tubulin–combretastatin A-4 binding site (PDB ID: 5LYJ) of tubulin. The binding affinities were found to be efficient, ranging from −6.502 to −8.341 kcal/mol, with two major electrostatic interactions observed: H-bond and halogen bond. Ligand 4i had a binding affinity of −8.149 kcal/mol with the tubulin–combretastatin A-4 binding site and displayed a H-bond interaction with the residue Asn258. The ADME and toxicity prediction studies for each compound were carried out using SwissADME and ProTox-II software. None of the compounds’ ADME predictions showed that they violated Lipinski’s rule of five. All of the compounds were also predicted to have LD50 values between 440 and 500 mg/kg, putting them all in class IV toxicity, according to the toxicity prediction. The current discovery could potentially open up the opportunity for further developments in cancer.